Revisit intention development model in tourist villages in Bali province Integration of theory of planned behavior and theory of stimulus organism response - Pratiwi, Komang Ary; Giantari, I Gusti Ayu Ketut; Sukaatmadja, I Putu Gde; etiawan, Putu Yudi S (Edelweiss Applied Science and Technology, 2025)
Bali, a popular tourist destination, is currently facing the challenge of overtourism. To address this issue, the Bali Provincial Government is promoting the development of alternative tourism that emphasizes culture, natural potential, and the environment, such as tourist villages. This initiative aims to distribute tourism more evenly and boost economic activity in Bali’s tourist villages. This study aims to analyze the factors influencing tourists’ intention to revisit a tourist village, focusing on Service Quality based on Tri Kaya Parisudha, Servicescape, Destination Image, and Tourist Satisfaction. The methodology employed is a mixed-method approach with an Exploratory Sequential Design, beginning with a Focus Group Discussion to identify Service Quality indicators based on Tri Kaya Parisudha, followed by a content validity test using the Content Validity Ratio, and descriptive and inferential statistical analysis using SEM-PLS. The research sample consisted of 290 respondents selected through purposive sampling. The results indicate that Service Quality based on Tri Kaya Parisudha, Servicescape, and Destination Image positively affect the intention to revisit, both directly and through the mediation of Tourist Satisfaction. These findings provide important implications for tourism village managers to enhance Service Quality based on the local wisdom of Tri Kaya Parisudha, thereby creating a unique identity, sustainability, and competitive advantage. Additionally, the study offers a reference for further research on the positive contributions of local wisdom in tourism.